2013
DOI: 10.1093/ageing/aft141
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a delirium predictive score in older people

Abstract: This simple predictive model highlights functional status and a proxy for dehydration as a useful tool for identifying older patients that may benefit from close monitoring and preventive care for early diagnosis of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…Raised serum urea or urea to creatinine ratio (used as a proxy for dehydration) was found to be significantly predictive of incident delirium, and authors have argued that these could form part of a simple screening tool [26,27]. Due to study resource constraints, we were only able to assess blood results for the admissions with delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raised serum urea or urea to creatinine ratio (used as a proxy for dehydration) was found to be significantly predictive of incident delirium, and authors have argued that these could form part of a simple screening tool [26,27]. Due to study resource constraints, we were only able to assess blood results for the admissions with delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Functional dependency has been measured in a number of ways, including through assessment of dependency using the Katz Activities of Daily Living (ADL) questionnaire [26,28,29]. However, by reporting functioning by difficulties with ADL, (dressing, feeding, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-established importance of this particular risk factor, it is somewhat surprising that it was not included in all models. Three other studies (27,28,31) included either advanced age or dependence in activities of daily living but not cognitive impairment. In addition, Douglas et al [28] found that brief screening for cognitive impairment on admission, that is, inability to spell WORLD backwards or answer orientation questions accurately, predicted delirium risk.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…As expected, model accuracy was lower in validation cohorts than in the populations from which they were derived. In the validation cohorts, Carrasco et al [31] pursued a different strategy, developing an equation for a "Delirium Predictive Score" that, when used with a particular cut point, produces positive and negative likelihood ratios thought to be clinically useful. For instance, with a pretest probability of 20%, the posttest probabilities of delirium for a negative and positive result are 3% and 45%, respectively.…”
Section: Model Performancementioning
confidence: 99%
See 1 more Smart Citation